Dinamika Formulasi Pemekaran Kecamatan Kandang Makmur dalam Wilayah Kota Lhokseumawe - Sofianus, T; Nazaruddin, M; Abubakar, Muhammad Bin (Program Magister Administrasi Publik, 2023)
The issue with the formation of the Kandang Makmur sub-district is that the conditions for political, territorial, and administrative aspects, such as the length of the design process and the discussion of regional expansion, are such that they are not met. The expansion of the Kandang Makmur District underwent a long process and involved many parties. According to David Easton, in the discussion process to analyze problems using political system theory in public policy formulation, which consists of input, withinput, and output, Researchers choose to use a qualitative approach because a qualitative approach is believed to be able to assist researchers in interpreting and describing the phenomena that occur. The sub-district expansion process in Kandang Makmur is full of political elements. The political element is the efforts of Mayor Suaidi Yahya and the Aceh Party to control the legislature and the expansion agenda of the Kandang Makmur sub-district. This is in accordance with the concept that in the policy-making process there is the use of interests and power in order to form a policy. So in the formulation process, there was a tug-of-war between the executive and the legislature. It is hoped that the Lhokseumawe DPRK, as the legislature, rationalizes the expansion policy of Kandang Makmur District by providing alternative policies to the executive, which is the party proposing the expansion policy of Kandang Makmur District. so that the next researcher can continue the discussion related to the implementation of the Qanun for regional expansion in Kandang Makmur District